2019
DOI: 10.1111/ijn.12779
|View full text |Cite
|
Sign up to set email alerts
|

Do surgical patients' characteristics and behaviours affect nurses' pain management decisions? A qualitative inquiry

Abstract: Background: Despite a growing body of literature investigating the impact of patients' age and sex differences on pain, there is little research on how patients' characteristics and behaviours affect nurses' pain management decisions. Aim: This study examined surgical nurses' views and experiences toward pain management in relation to the patients' characteristics and behaviours in a Jordanian university hospital. Methods: Focus group discussions (n = 4) were used with a convenience sample of 27 female Registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For instance, some students had a negative clinical experience when a patient's relatives or visitors looked at nurses as housemaids. Earlier research found that some patient relatives and their poor communication with nursing staff affect the work pattern negatively at the ward level (Shoqirat, Mahasneh, Singh, Al Hadid, et al, 2019;Shoqirat, Mahasneh, Singh, Al-Sagarat, et al, 2019). Although nursing worldwide and in Jordan has gained increasing social respect, it seems that students' image has a profound impact on students' first clinical placement and thus, professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some students had a negative clinical experience when a patient's relatives or visitors looked at nurses as housemaids. Earlier research found that some patient relatives and their poor communication with nursing staff affect the work pattern negatively at the ward level (Shoqirat, Mahasneh, Singh, Al Hadid, et al, 2019;Shoqirat, Mahasneh, Singh, Al-Sagarat, et al, 2019). Although nursing worldwide and in Jordan has gained increasing social respect, it seems that students' image has a profound impact on students' first clinical placement and thus, professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also reported to nurses for assistance in coping with their pain, nurses offered support by administration of pain medications, engaging them in conversations and activities to divert their minds of the pain as well as the use of words of encouragement in helping patients cope with their pain. At the forefront of postoperative pain management are nurses as they play a significant role in the assessment, implementation and evaluation of pain management interventions (42,28) nurses spend 24 hours with the patient, it is therefore not surprising they are the main source of support to participants in coping with their post-operative pain. The fact that patients report their postoperative pain to nurses for support in coping with their post-operative pain in this study is in line with a study conducted by (43) in which it was seen that post-operative patients felt nurses were available and hence sort for help from them in managing their postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently reported within nursing pain research are the existence of gaps between what nurses say they do for pain and what is provided for the patient (Dihle et al, 2006; Wikström et al, 2014). Underpinning this are erroneous ageist beliefs held by nurses about the older person as not complaining of their pain (Coker et al, 2010) and due to their age, they are able to cope better when in pain (Shoqirat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%